Implementation of Change Management in Shaping Student Character in the MAPK Program at MAN 1 Yogyakarta - Nudin, Burhan; Salsabil, Shoffiyah; Zainuddin, Nurkhamimi; Septianto, Mukhammad Eko; Husain, Andi Musthafa; Saputra, Nadar (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This article discusses the implementation of change management in character education at MAN 1 Yogyakarta, focusing on developing skilled individuals with leadership qualities and the ability to tackle global competition challenges. In the current evolving landscape, where global competition has intensified, students in Indonesia are facing demanding requirements. This research is a case study using a qualitative descriptive method. Besides academic excellence, students also need to possess